Antimicrobial and protective effects of non-thermal plasma treatments on the performance of a resinous liner. (September 2020) - Nagay, Bruna Egumi; Bitencourt, Sandro Basso; Commar, Betina Chiarelo; da Silva, Emily Vivianne Freitas; dos Santos, Daniela Micheline; Rangel, Elidiane Cipriano; Goiato, Marcelo Coelho; Del Bel Cury, Altair Antoninha; Ricomini-Filho, Antônio Pedro; Barão, Valentim Adelino Ricardo
Graphical abstract: Highlights: Non-thermal plasmas (NTP) were tested in a critical biofilm inhibition challenge. HMDSO- and SF6 - based NTP reduced C. albicans on liner after 14 days of biofilm. HMDSO also showed stability and enhanced physico-chemical properties of the liner. HMDSO has potential to control fungal infections besides improve liner properties. Abstract: Objective: Overcoming substantial shortcomings of soft liners as physico-chemical changes and liner-biofilm-related infections remains a challenge in the rehabilitation treatment. In this study, protective non-thermal plasma (NTP) treatments were developed on the soft liner surface to improve its surface and physico-chemical properties and to reduce fungal colonization after biofilm inhibition challenge. Methods: Resinous liner specimens (Coe-Soft) were prepared and distributed in 3 groups according to the surface treatments: (1) untreated (control); (2) treated with sulfur hexafluoride-based NTP (SF6 ); and (3) treated with hexamethyldisiloxane-based NTP (HMDSO). To test the NTP stability and their protective and antimicrobial effect on the liner surface over time, the morphology, chemical composition, roughness, water contact angle, shore A hardness, sorption and solubility were evaluated before and after the specimens were exposed to dual-species biofilm of Candida albicans and Streptococcus oralis for 14 days. Colony forming units and biofilm structure were assessed. Data were submitted to ANOVA and Tukey tests (α = 0.05). Results: Both treatments modified the surface morphology, increased hydrophobicity and roughness of the liner, and were effective to reduce C. albicans adhesion without affecting the commensal health-associated S. oralis . HMDSO presented chemical stability and lower hardness in both periods, whereas SF6 exhibited higher initial hardness than control and the highest sorption; contrarily, similar solubility was noted for all groups. Conclusion: HMDSO-based film showed improved physico-chemical properties and inhibited C. albicans biofilm. Thus, it has potential for use to control candida-related stomatitis and improve liner's stability even after being exposed to biofilm inhibition challenge.